Somatostatin in the Periventricular Nucleus of the Female Rat: Age Specific Effects of Estrogen and Onset of Reproductive Aging - Beek, Eline M. Van der; Vugt, Harmke H. Van; Schepens-Franke, Annelieke N.; Heijning, Bert J.M. Van de (IntechOpen, 2012)
None